Certificate of Accreditation for Master of EnvironmentalS cience( LandU sea nd Water Resource Management-) Formerly known as Master of Science( Land Use and Water Resource Management) - Universiti Malaysia Sarawak (Universiti Malaysia Sarawak (UNIMAS), 2013)
Certificate of Accreditation for Master of EnvironmentalS cience( LandU sea nd Water Resource Management-) Formerly known as Master of Science( Land Use and Water Resource Management) has attained the quality assurance standards set by the agency and is in compliance with the Malaysian qualifications framework Level 7. Date of Accreditation : 11/09/2013